Metabolomics As a Tool for the Characterization of Drug-Resistant Epilepsy - Murgia, Federica; Muroni, Antonella; Puligheddu, Monica; Polizzi, Lorenzo; Barberini, Luigi; Orofino, Gianni; Solla, Paolo; Poddighe, Simone; Del Carratore, Francesco; Griffin, Julian L.; Atzori, Luigi; Marrosu, Francesco (Frontiers in Neurology, 2017)
Purpose: Drug resistance is a critical issue in the treatment of epilepsy, contributing to clinical emergencies and increasing both serious social and economic burdens on the health system. The wide variety of potential drug combinations followed by often failed consecutive attempts to match drugs to an individual patient may mean that this treatment stage may last for years with suboptimal benefit to the patient. Given these challenges it is valuable to explore the availability of new methodologies able to shorten the period of determining a rationale pharmacologic treatment. Metabolomics could provide such a tool to investigate possible markers of drug resistance insubjects with epilepsy. Methods:Blood samples were collected from: 1)controls (C) (n=35), 2)patients with epilepsy “responder”(R) (n=18) and 3) patients with epilepsy “non-responder” (NR) (n= 17) to the drug therapy. The samples were analysed using NMR spectroscopy, followed by multivariate statistical analysis. Key Findings: A different metabolic profile based on metabolomics analysis of the serum was observed between controls and patients with epilepsy, and also between responder and non-responder patients. It was possible to identify the discriminant metabolites for the 3 classes under investigation.Serum from patients with epilepsy were characterized by increased levels of 3-OH-butyrate, 2-OH-valerate, 2-OH-butyrate, acetoacetate, acetone, acetate, choline, alanine, glutamate, scyllo-inositol (C<R<NR) and decreased concentration of glucose, lactate, citrate compared to controls (C>R>NR). Significance: In conclusion, metabolomics may represent an important tool for discovery of differences between subjects affected by epilepsy responding or resistant to therapies and for the study of its pathophysiology, optimizing the therapeutic resources and the quality of life of patients.